2022
DOI: 10.7717/peerj.13239
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of soil nutrients and evaluation of cultivated land in Xuwen county

Abstract: It is of great significance to promote the quantitative research of soil science and the implementation of precision agriculture. On this basis, taking Xuwen County as the research object, this paper comprehensively analyzed the soil characteristics of cultivated land in Xuwen County and clarify the soil nutrient content and spatial distribution characteristics of cultivated land in Xuwen County, this paper comprehensively applied the methods of geostatistics, geographic information system (GIS) and fuzzy math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…For SOM, TN, AP, and AK, the nugget-to-sill ratios were between 25% and 75%. This demonstrated that the soil nutrients in this research exhibited a medium spatial correlation [27] and that the spatial variability of the samples was driven by a combination of random factors, like irrigation, fertilization, and soil improvement, and structural factors, like climate, topography, and soil type [36]. The amount of spatial dependency in the soil nutrient distribution was assessed using variogram analysis.…”
Section: Variogram Analysismentioning
confidence: 73%
See 1 more Smart Citation
“…For SOM, TN, AP, and AK, the nugget-to-sill ratios were between 25% and 75%. This demonstrated that the soil nutrients in this research exhibited a medium spatial correlation [27] and that the spatial variability of the samples was driven by a combination of random factors, like irrigation, fertilization, and soil improvement, and structural factors, like climate, topography, and soil type [36]. The amount of spatial dependency in the soil nutrient distribution was assessed using variogram analysis.…”
Section: Variogram Analysismentioning
confidence: 73%
“…Human activities increasingly influence natural factors and have a direct impact on the soil nutrient content. The amount of chemical fertilizers applied directly affects the nutrient content in the soil, thus causing a substantial variation in soil nutrient heterogeneity [36]. This has shown that the extent of human activity disturbing the distribution of soil nutrients should be a key focus.…”
Section: Spatial Distribution and Impact Factorsmentioning
confidence: 99%
“…Soil nutrients are essential elements and compounds in the soil, and include common elements such as nitrogen, phosphorus, and potassium, as well as trace elements such as iron, zinc, and copper. Multiple studies have shown that soil nutrients play a crucial role in plant growth and development [ 49 , 50 ] and can influence the biosynthesis and accumulation of plant secondary metabolites [ 51 , 52 ]. In Camellia sinensis , a deficiency of soil nutrients can lead to the downregulation of the protochlorophyllide oxidoreductase-encoding gene, which is involved in chlorophyll biosynthesis, ultimately resulting in leaf yellowing [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the southern region with undulating terrain and many hills was noted to be dominated by yellow brown soil and red soil, which presented characteristics such as low soil pH, sandy soil texture, poor living environment for soil microorganisms, weak water storage capacity of soil, low organic matter content, and nearly low content of potassium and phosphorus. Besides, the southern soil also exhibited mild and moderate erosion, which can exert serious effects on the growth of crops [81].…”
Section: Spatial Distribution Characteristics and Pattern Of Shmentioning
confidence: 99%